"Be Prepared if I Bring It Up:" Patients' Perceptions of the Utility of Religious and Spiritual Discussion During Genetic Counseling. Issue 5 (13th January 2016) - Thompson, Amanda Bartenbaker; Cragun, Deborah; Sumerau, J. E.; Cragun, Ryan T.; De Gifis, Vanessa; Trepanier, Angela
Abstract: As debates continue about the relevance of religion to health care, research is needed to guide decisions about whether genetic counselors (GCs) should routinely address religious and/or spiritual (R/S) issues with their patients. We conducted an online survey to gauge patient perspectives on this issue. Among the 70 respondents, frequencies of closed‐ended responses and thematic analyses of open‐ended responses revealed multiple patient concerns related to R/S discussions with GCs. Although 60 respondents reported being R/S, only a small minority would want to discuss R/S issues if it meant less time discussing medical information. Most respondents also expressed opinions that: 1) genetic counseling should be about science; 2) GCs are not qualified to discuss R/S issues; 3) other outlets are available to meet the needs of patients who want R/S counseling; and/or 4) R/S discussions are more likely to be acceptable if patients broach the topic or in specific circumstances (e.g., when patients are facing end‐of life issues). Overall, responses suggest routine or comprehensive R/S assessments or discussions are not necessary and that GCs would be best equipped to help all their patients if they were prepared to listen, be supportive, and make referrals when R/S issues arise in clinic.